К вопросу оптимального проектирования пластин - Токарева, О.Н. (Теорія оптимальних рішень, 2005)
The paper proposes an optimisation model for mechanical constructions described by the second order partial differential equation system with respect to moments and plate deflection. The paper aso considers conjugated boundary-value problems for finding derivatives model functionals as for a control function. A theorem about existense and uniqueness of a solution to a conjugated boundary-value problem is formulated. The PLAT-algorithm is described that is used to solve the present model on the basis of barrier functions.